High‐Voltage and Super‐Stable Aqueous Sodium–Zinc Hybrid Ion Batteries Enabled by Double Solvation Structures in Concentrated Electrolyte. Issue 7 (24th May 2021) - Ao, Huaisheng; Zhu, Weiduo; Liu, Mengke; Zhang, Wanqun; Hou, Zhiguo; Wu, Xiaojun; Zhu, Yongchun; Qian, Yitai
Abstract: Aqueous sodium–zinc hybrid ion batteries are attracting extensive attention due to high energy density, low cost, and environmental friendliness. Unfortunately, there are still some drawbacks associated with the low voltage and cycle performance degradation that limit their practical application. Here, a concentrated aqueous electrolyte with solvation‐modulated Zn 2+ is reported that reduces the hydrogen evolution reaction on the surface of Zn metal, avoiding the generation of ZnO and uneven deposition. Accordingly, the Zn anode exhibits 1600 h Zn plating/stripping and ≈99.96% Coulombic efficiency after 700 cycles. In addition, solvation‐modulated Na + promotes the excellent structural stability of zinc hexacyanoferrate (ZnHCF) due to the rhombohedral–rhombohedral rather than rhombohedral–cubic phase transition. A ZnHCF//Zn full cell delivers an average voltage of 1.76 V and 98% capacity retention after 2000 cycles at 5 C rates. Abstract : The concentrated aqueous electrolyte with novel Zn 2+ solvation structure suppresses the hydrogen evolution reaction on the surface of Zn anode, facilitating reversible Zn plating/stripping. The anion‐enriched inner Helmholtz plane and co‐insertion/extraction of Na + and H2 O guarantee the praiseworthy stability of zinc hexacyanoferrate (ZnHCF) cathode. A ZnHCF//Zn full cell delivers 98% capacity retention after 2000 cycles at 5 C rates.